4- State-in-Society: the Mutual Constitutiveness of the Developmental State and Higher Education in South Africa - Thaver, Beverly; Thaver, Lionel (African Sociological Review, 2009)
Seeking to go beyond the pessimism and reification of contemporary analyses of the state in Africa, this article applies Migdal’s State in Society (2001) approach to the field of higher education transformation in South Africa. It argues that the state is best understood through its actual practices, particularly at those points where it reaches into society through policy implementation and, conversely, where society through its institutions in turn reaches into the state. In the course of these engagements, social boundaries are constituted through alliances, accommodations and resistances and have a mutually transformative effect on both state and society. The article shows how, with regard to both the image and the practices of the state, the relationship between the developmental state and higher education in South Africa reveals a range of tensions around issues such as accountability, autonomy, transformation and globalisation; and it concludes that Migdal’s approach offers a fruitful theoretical corrective to state-centric and socio-centric views of the state-society relationship